Resistive switching behaviour of a tantalum oxide nanolayer fabricated by plasma oxidation. Issue 4 (11th February 2013) - Tang, G. S.; Zeng, F.; Chen, C.; Gao, S.; Fu, H. D.; Song, C.; Wang, G. Y.; Pan, F.
Abstract We investigate the resistive switching behaviour of a tantalum oxide nanolayer‐based nonvolatile memory with Pt/TaO5–x/TaN structure, which was prepared at room temperature through a processing compatible with CMOS technology. The tantalum oxide nanolayer with thickness of about 5 nm was fabricated by plasma oxidation of TaN films. The switching mechanism can be explained by the modulation of the local oxygen‐deficient conduction channel resulting from oxygen ions drift. This Letter represents a cost‐efficient method for developing nanoscale restive switching nonvolatile memories. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)